An Analysis of Suitable Thai Songs for Early Childhood from Songs of Siam for Children - Disua, Pattera; Laovanich, Vitchatalum (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research aims to analyze musical elements aspect, and select suitable Thai songs for early childhood in Song of Siam for children. The researcher analyzed musical elements aspect, and selected 16 Thai songs in Song of Siam for children. The data was collected by Vocal music analysis form, and criteria for selecting songs. The result of this research found that four songs are consistent with criteria for selecting songs which were created by researchers at a high level, including Wan Koet, Toi Taring, Nok Khao Khan Chuk Kru, and Krao Nok. Nine songs are consistent with criteria for selecting songs in moderate level, including Sansoen Phrabarami, Hong Thong, Kakoei, Rong Mae Sri, Rong Chua, Thep Thong, Supannahong, Ngam Saeng Duan, and Khun Duan Ngai. Three songs are consistent with criteria for selecting songs at a fair level, including Chat, Klom Dek, and Non Ning Ning.